Literature and the experience of the foreign language - Martin Bygate (Ilha do Desterro)
The two quotations above, one by a literaty critic, the other by a specialist in language learning, agree on one important point: that in language learning as in literature, the choice of expression is itself significant. In reflections on the learning of a foreign language and its literature, it is appropriate to consider the relationship between literary and non-literary language. Too often these two manifestations of language are considered distinct. Our academic discussions of the two areas are, significantly, themselves couched in two quite different types of language, creating a terminological frontier which neither side dares to cross. Whether this is in fact desirable for the two areas is one question that this article intends to discuss. Another is whether the division is healthy for the student who strays into our respective territories.